From Northern Rhodesia to Zambia : Recollections of a DO/DC 1962-73 - Bond, Mick (UPCC book collections on Project MUSE. History Supplement., 2014)
Mick Bond spent the years 1962-73 as a District Officer and a District Commissioner, actively participating in the demise of the colonial regime and then as a civil servant in independent Zambia.